Biomarkers predicting the effectiveness of normobaric altitude training - Simon Klügel; Svenja Nolte; Sebastian Hacker; Tom Kastner; Nico Walter; Daniel Fleckenstein; Celina Maier; Kristina Gebhardt; Angela Relogio; Deeksha Malhan; Anna Klemmer; Tobias Stauber; et al. (European Journal of Applied Physiology, 2026)
Purpose The aim of the present study was to identify blood-based biomarkers that could predict individual VO 2 max improvement before the start of an artificial altitude training camp. Methods In an exploratory intervention study, 15 young highly trained athletes from the German Athletics Federation completed a 21-day Live High – Train Low program at an artificial altitude house, which simulated an altitude of 800 km·h (approximately 1.900–2.500 m) under normobaric hypoxia. V̇O₂max was measured pre- and post-intervention, and blood parameters were collected at six time points (pre, post and four times at altitude. The pre measurement functioned as baseline and was used for the predictive model. Results Altitude training led to a mean V̇O₂max increase of 2.1 mL · kg⁻¹ · min⁻¹ (+ 3.1%), with high interindividual variability (–1.7 to + 4.5 mL · kg⁻¹ · min⁻¹). Neither training load, sex, nor discipline explained these differences. Logistic regression analyses identified monocyte percentage (> 10%) and neutrophil percentage (> 50%) emerged as the strongest predictors of responder status (McFadden’s R² = 0.61 and 0.65, respectively), while neutrophil-to-lymphocyte-ratio (NLR) and hematocrit also showed significant predictive value. Threshold analyses revealed that high-responders consistently displayed lower neutrophil activity (NLR < 1.5) and higher hematocrit levels (> 42.5%), in contrast to low-responders. Longitudinal biomarker trajectories further supported these distinctions, with high-responders maintaining adaptive immune and iron-related profiles, whereas low-responders exhibited persistent signs of innate immune activation and suboptimal erythropoietic status. Conclusion These results highlight the relevance of functional biomarker profiles for individualized training planning in elite sports. Practically, this opens new possibilities for the targeted use of altitude training while minimizing health risks.

Correction: Vitamin D status and its determinants in German elite athletes - Sebastian Hacker; Claudia Lenz; Lukas Reichert; Robert Ringseis; Karen Zentgraf; Karsten Krüger (European Journal of Applied Physiology, 2025)

Vitamin D status and its determinants in German elite athletes - Sebastian Hacker; Claudia Lenz; Lukas Reichert; Robert Ringseis; Karen Zentgraf; Karsten Krüger (European Journal of Applied Physiology, 2025)
Purpose This study investigated elite German athletes to (1) assess their serum 25(OH)D levels and the prevalence of insufficiency, (2) identify key factors influencing serum 25(OH)D levels, and (3) analyze the association between serum 25(OH)D levels and handgrip strength. Methods In this cross-sectional study, a total of 474 athletes (231 female), aged 13–39 years (mean 19.3 years), from ten Olympic disciplines were included. Serum 25(OH)D levels were analyzed via liquid chromatography–mass spectrometry, and 17 single nucleotide polymorphisms (SNPs) related to vitamin D metabolism were determined using leukocyte DNA. Grip strength was measured unimanually using a hand-held dynamometer. Multiple linear regressions were used to analyze the influence of SNPs, age, sex, season (summer vs. winter), and discipline (indoor vs. outdoor) on 25(OH)D status. Linear regression analyzed the relationship between handgrip strength and serum 25(OH)D levels. Results In total, 55.5% ( n = 263) of athletes demonstrated insufficient serum 25(OH)D levels (< 30 ng/mL, < 75 nmol/L), with 16% ( n = 76) showing levels below 20 ng/mL (50 nmol/L). After correction for multiple testing, significant influences on 25(OH)D levels were observed for the C allele of VDBP rs7041 (AC Genotype: $$\widehat{\upbeta }$$ β ^ = 7.46, p < .001; CC Genotype: $$\widehat{\upbeta }$$ β ^ = 6.23, p = .001). Age (all p < .01) and discipline (indoor vs. outdoor; all p < .05) also influenced serum 25(OH)D levels. Furthermore, serum 25(OH)D was positively associated with handgrip strength ( $$\widehat{\upbeta }$$ β ^ = 0.01, p < .001). Conclusion A high prevalence of insufficient 25(OH)D levels (< 30 ng/mL, < 75 nmol/L) was observed. We identified certain genetic variants as well as age and discipline as predictors of serum 25(OH)D levels. This knowledge may guide individualized diagnostic, nutritional, and supplementation strategies.

Chemical looping of synthetic ilmenite, Part I: Addressing challenges of kinetic TGA measurements with H 2 - Thomas Steiner; Kai Schulze; Norbert Kienzl; Magdalena Pauritsch; Viktor Hacker; Sebastian Bock; Alberto Abad; Robert Scharler; Andrés Anca-Couce (Fuel, 2024)

Acute response of biomarkers in plasma from capillary blood after a strenuous endurance exercise bout - Thomas Reichel; Steffen Held; Anthony Schwarz; Sebastian Hacker; Fabian Wesemann; Lars Donath; Karsten Krüger (European Journal of Applied Physiology, 2023)
Purpose The present study aims to investigate the acute response of potential exercise-sensitive biomarkers in capillary plasma to an acute incremental running test. In a second step, their concentration was compared to the changes in the venous serum. Methods Thirty-seven active young female and male adults completed a VO 2max ramp test on a treadmill. Before and after exercise, capillary blood from the earlobe and venous blood were taken and synchronized. Concentrations of Interleukin- (IL-) 1β, IL-1ra, IL-6, IL-8, IL-17A, Interferon (IFN)-y, CC-chemokine ligand (CCL)-2, Matrix metallopeptidase (MMP)-9, Secreted protein acidic and rich in cysteine (SPARC), Cluster of differentiation (CD)163, S100 Ca 2+ -binding protein (S100) A8, S100A9, S100B, Brain-derived neurotrophic factor (BDNF), and Myeloperoxidase (MPO) were determined by magnetic bead-based multiplex assay. Results Capillary plasma concentrations of IL-1β, IL-6, IL-8, IL-17A, IFN-y, CCL-2, MMP-9, SPARC, CD163, S100A9, S100B, and BDNF increased after exercise ( p < 0.05). Comparing the values from capillary plasma and venous serum, ICCs classified as good were found for IFN-y (post), while the ICCs for IL-1β, IL-8, IL-17A, CCL-2, MMP-9 (post), SPARC, and BDNF (post) were classified as moderate. For all other parameters, only weak ICCs were found. Conclusion As in the venous serum, there was an increase in most markers in the capillary plasma. However, acceptable to low associations can be found in the concentration levels of these proteins between the compartments. Thus, this source of blood sampling could find some biomarker applications in sports practice.

Task-relevant brain networks identified with simultaneous PET/MR imaging of metabolism and connectivity - Andreas Hahn; Gregor Gryglewski; Lukas Nics; Lucas Rischka; Sebastian Ganger; Helen Sigurdardottir; Chrysoula Vraka; Leo Silberbauer; Thomas Vanicek; Alexander Kautzky; Wolfgang Wadsak; Markus Mitterhauser; et al. (Brain Structure and Function, 2017)